Physical Activity, Nutrition, Cognition, Neurophysiology, and Short-Time Synaptic Plasticity in Healthy Older Adults: A Cross-Sectional Study - Schättin, Alexandra; Gennaro, Federico; Egloff, Martin; Vogt, Simon; Bruin, Eling D. de (Frontiers in Aging Neuroscience, 2018)
The aging brain undergoes remodelling processes because of biological and environmental factors. To counteract brain aging, functional plasticity should be preserved. The aim of this study was to evaluate the capacity of generating short-time synaptic plasticity in older adults and explain the individual capacity by physical activity, nutritional habit, cognition, and neurophysiological functioning. We hypothesized that the capacity of generating short-time synaptic plasticity in the motor cortex is heterogeneous and this heterogeneity can be explained by physical activity, nutritional habits, cognition, and neurophysiological functioning. Thirty-six participants (mean age 73.3 ± 5.9 years) received transcranial magnetic stimulation in combination with peripheral nerve stimulation to experimentally induce short-time synaptic plasticity by paired associative stimulation (PAS). Adaptations in neuronal excitability were assessed by motor evoked potential (MEP) in the right m. tibialis anterior before and after PAS. The Physical Activity Questionnaire 50+ and the StepWatchTM captured physical activity. Nutritional status was assessed by the Mini Nutritional Assessment. Cognition was assessed by reaction time for a divided attention test and with the Montreal Cognitive Assessment. Neurophysiological functioning was assess by electroencephalography measurements during the aforementioned divided attention test. Results showed that MEPs of the highest stimulation intensity and the slope of recruitment curve showed significant differences comparing before, 5min after, or 30min after PAS (p < .05). Visual inspection of the individual recruitment curve slopes over the three-time points indicated four different response types, however, response groups did not significant differ based on physical activity, nutritional status and cognition. In a second-level analysis, participants having an increased slope showed a significant higher energy expenditure compared to the participants having a decreased slope (z = -2.101, p = .036). This study hints towards older adults differing in their neuronal excitability which is strongly associated to their short-time synaptic plasticity levels, and that a physical active lifestyle seems to some extent influence the capacity of generating LTP-like synaptic plasticity in older adults. Future studies should consider more sensitive behavioral assessments and bigger sample sizes to get a broad scope of the older adults’ population.